2010
DOI: 10.5032/jae.2010.03053
|View full text |Cite
|
Sign up to set email alerts
|

Defining Agricultural Education Instructional Quality

Abstract: Current legislation, theory and concepts build the framework for this study in understanding how quality instruction is defined in education in general. In particular, the Fenstermacher and Richardson (2005) definitions of good, quality and successful teaching were used as the lens to interpret the findings. The study takes an exploratory approach at answering "what are specific indicators of quality instruction in a school based agricultural education program?" by using the consensus-building Delphi technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…This transfer of skills acquired by students through experiential learning is an important theme associated with secondary agricultural education, i.e., preparing students for entry-level careers in the agricultural industry. Jenkins and Kitchel (2010) found that quality SAE programs are contingent upon two factors: goal setting and student satisfaction. Specifically, a quality SAE program involves students who set goals proactively for their SAE.…”
Section: Stated Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…This transfer of skills acquired by students through experiential learning is an important theme associated with secondary agricultural education, i.e., preparing students for entry-level careers in the agricultural industry. Jenkins and Kitchel (2010) found that quality SAE programs are contingent upon two factors: goal setting and student satisfaction. Specifically, a quality SAE program involves students who set goals proactively for their SAE.…”
Section: Stated Thatmentioning
confidence: 99%
“…Further, because a major finding of this study was that these AC teachers expected their students to own and manage their SAE programs, it is important to determine how these teachers are evaluating these programs and the effect they are having on students regarding their career and life preparation. Jenkins and Kitchel (2010) suggested that teachers should assist students in developing realistic and attainable SAE program goals. Therefore, professional development is warranted to assist AC teachers in developing plans, per a SAE policy statement, for helping students set and achieve their individual SAE program goals.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…For relativists in this study, learning is all about the journey to understanding. The principles underlying this epistemological stance could be considered consistent with indicators for quality instruction in agricultural education where teachers should use variability in instructional practices (Jenkins et al, 2010). Since relativists believe learning is a process, using a variety of instructional practices naturally lends itself to this epistemological belief.…”
Section: Conclusion Recommendations and Discussionmentioning
confidence: 99%
“…For example, they described their teaching approach as one that would promote an atmosphere where students would be able to construct their own knowledge from experiences. Educational scholars suggest that teachers should use similar approaches (Calderhead & Robson, 1991;Jenkins et al, 2010;Kagan, 1992;Pajares, 1992). For example, highly quality teachers are often depicted as facilitators of the learning process rather than authority figures that hold the ultimate truth (Calderhead & Robson, 1991;Jenkins et al, 2010;Kagan, 1992;Pajares, 1992).…”
Section: Conclusion Recommendations and Discussionmentioning
confidence: 99%
“…Nevertheless, little attention appears to have been devoted to increasing its use. The problem is further complicated if considering the various characteristics and roles that school-based, agricultural education (SBAE) teachers must fulfill to be considered effective (Jenkins III & Kitchel, 2010;Roberts & Dyer, 2004). In SBAE, instructors are expected to facilitate learning through classroom and laboratory instruction in and about agriculture for students (National Research Council, 1988), advise students' supervised agricultural experiences (SAE) as individualized projects, and manage their participation in the National FFA Organization (FFA).…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%